2015
DOI: 10.1590/1679-78251630
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic crushing of uniform and density graded cellular structures based on the circle arc model

Abstract: A new circle-arc model was established to present the cellular structure. Dynamic response of models with density gradients under constant velocities is investigated by employing Ls-dyna 971. Compared with the uniform models, the quasi-static plateau stress of different layers seems a significant parameter correlated with the deformation mode except for inertia effect when the density gradient is introduced. The impact velocity becomes much more vital on the deformation of the unit cell than the density gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
(51 reference statements)
1
13
0
Order By: Relevance
“…This phenomenon could also be found in our previous work in Ref. [26] by constructing the local strain field. So the stress of 0.02 β = at stationary side is close to the quasi-static crushing stress of the weakest layer and will increase sharply when the wave front reaches the stationary side.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 82%
See 3 more Smart Citations
“…This phenomenon could also be found in our previous work in Ref. [26] by constructing the local strain field. So the stress of 0.02 β = at stationary side is close to the quasi-static crushing stress of the weakest layer and will increase sharply when the wave front reaches the stationary side.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 82%
“…Zhang et al [26] established a circle-arc model and investigated the response of the regular graded cellular material. Results showed that introducing density functional gradation in hexagonal honeycombs brought about new deformation patterns due to changes in material distribution and preferential cell wall collapse of the weaker members [27].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Their results show that the elastic modulus and yield strength of cellular structures increase with the increasing of density. Dynamic behaviors of Voronoi model (Zhang et al, 2016) and circle-arc model (Zhang et al, 2015) with density gradient subjected to constant velocity impact were simulated and analyzed and three deformation modes were observed to be velocitydependent. Numerical simulations were carried out to verify the predictions of the theoretical analysis of the propagation of stress waves in cellular solids with non-uniform density to deepen the understanding of their dynamic compaction due to impact loading (Karagiozova and Alves, 2015).…”
mentioning
confidence: 99%